Produk Kerajinan Bordir Di Nagari Ulakan Padang Pariaman Sumatera Barat - Ranelis, Ranelis; Hayani, Wirda; Washinton, Rahmad; Haq, Chairul (SPACEPRO: Product Design Jurnal, 2024)
The article with the title "Embroidery Products in Nagari Ulakan Padang Pariaman, West Sumatra", aims to describe embroidery products in Nagari Ulakan. This study used qualitative research methods. Data collection techniques were carried out by means of observation, interviews and documentation. The research results obtained are that the embroidery craft products produced in this area are mukena or talakuang by placing the arise son flower,  the hibiscuse series motif as decoration. The motifs are placed on the head, neck, back and around the bottom edge of the mukena or talakuang.